Analisis Kemampuan Berpikir Kritis Matematis Siswa Berdasarkan Soal Berbasis TIMSS - Enjelica Natalia E Napitu; Mangaratua M. Simanjorang (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2023)
This research aims to determine the analysis of students' mathematical critical thinking abilities based on questions based on TIMSS VIII SMP Negeri 29 Medan. This research is descriptive qualitative research. The subjects in this research were 33 students in class VIII-7 of SMP Negeri 29 Medan. The results of the research show that: (1) The average value of students' interpreting abilities is 76.01, which indicates that students' interpretation indicators are in the high category. (2) The average student score in analyzing the mathematical critical thinking ability test is 64.39, which shows that the students' analysis indicators are in the medium category. (3) The average score of students' abilities in the evaluation indicators on the mathematical critical thinking ability test is 41.48, which shows that the students' evaluation indicators are in the low category. So it is concluded that students with high abilities are only able to fulfill 2 critical thinking indicators, namely interpreting and analyzing indicators, 2 students with moderate mathematical abilities are only able to fulfill 2 critical thinking indicators and students with low mathematical abilities, there is 1 student only fulfilling 1 critical thinking indicator in One of the question numbers is the evaluating indicator in question number 3.